Disease alleviating effects following prophylactic lemon and coriander essential oil treatment in mice with acute campylobacteriosis - Mousavi, Soraya; Weschka, Dennis; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2023)
Introduction Given the worldwide increasing prevalence of human Campylobacter jejuni infections and the emergence of multi-drug resistant enteropathogenic strains, antibiotic-independent approaches applying non-toxic natural compounds for the treatment and prophylaxis of campylobacteriosis appear utmost desirable. In our placebo-controlled intervention study, we surveyed potential disease-alleviating including anti-pathogenic and immune-modulatory effects upon prophylactic oral application of lemon-essential oil (LEM-EO) and coriander-essential oil (COR-EO) in acute experimental campylobacteriosis. Methods Therefore, secondary abiotic IL-10−/− mice were orally challenged with either LEM-EO or COR-EO starting seven days prior to peroral C. jejuni infection. Results and discussion Six days post-infection, slightly lower pathogen loads were assessed in the colon of mice from the LEM-EO as opposed to the COR-EO cohort if compared to placebo counterparts. Prophylactic application of both EOs improved the clinical outcome of acute campylobacteriosis which was paralleled by less distinct pathogen-induced colonic epithelial cell apoptosis. Moreover, mice subjected to LEM-EO and COR-EO prophylaxis displayed lower colonic numbers of macrophages/monocytes and of T lymphocytes, respectively, whereas in both verum groups, basal IL-6 and IFN-γ concentrations were measured in mesenteric lymph nodes on day 6 post-infection. The oral challenge with either EOs resulted in diminished secretion of distinct pro-inflammatory mediators in the kidney as well as serum samples derived from the infected mice. In conclusion, the results from our preclinical in vivo study provide evidence that LEM-EO and COR-EO constitute promising prophylactic measures to prevent severe campylobacteriosis which may help to reduce the risk for development of post-infectious sequelae in C. jejuni infected individuals.